IT SERVICE MANAGEMENT SYSTEM AT THE CENTRAL STATISTICAL AGENCY OF NORTH SULAWESI PROVINCE USES EXTREME PROGRAMMING METHODS BASED ON WEBSITE - Supit, Mesiasi Anjelika; Rantung, Vivi Peggie (Informatika, Universitas Jenderal Soedirman, 2024)
Information technology is required to enhance efficiency and effectiveness in various operational and service aspects. The research goal is to facilitate employees in submitting IT device maintenance requests and to facilitate IT service administrators at the North Sulawesi Provincial Statistics. The method used is the Extreme Programming method. The Extreme Method Programming has several stages, including planning, system design, coding, and testing. The prepared Management System IT can easily facilitate the employees of BPS North Sulawesi Province to simplify by monitoring and managing IT-related issues and resolving problems related to the manual reporting of goods.